Shakespeare on stage and off - Graham, Kenneth J. E. (Kenneth John Emerson), 1960-; Kolentsis, Alysia, 1976- (McGill-Queen'sUniversity Press, 2019)
"Today, debates about the cultural role of the humanities and the arts are roiling. Responding to renewed calls to reassess the prominence of canonical writers, Shakespeare On Stage and Off introduces new perspectives on why and how William Shakespeare still matters. Lively and accessible, the book considers what it means to play, work, and live with Shakespeare in the twenty-first century. Essays engage with contemporary stagings of his plays to explore the effect of performance practices on understandings of identity, death, love, race, gender, class, and culture. Providing an original approach to thinking about Shakespeare, other essays ask how the knowledge and skills associated with working lives can illuminate the playwright's works. Contributors look at ways of interacting with Shakespeare in the digital age, from film and television to live theatre broadcasts, social media, and online instructional tools. Together, the essays in this volume speak to how Shakespeare continues to enrich contemporary culture. A timely guide to the ongoing importance of Shakespearean drama, Shakespeare On Stage and Off surveys recent developments in performance, adaptation, popular culture, and education."--